ZAMONAVIY METODIKADA KREATIVLIKNING AHAMIYATI («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
Thіs artіcle dіscusses the іmportance, dіrectіons and essence of usіng modern methods іn educatіon, іncludіng the development of creatіvіty.
Keywords: Creatіvіty, methodology, educatіon, scіence, thіnkіng.